FUNGSI LEMBAGA PERMASYARAKATAN WANITA SEBAGAI UPAYA PERLINDUNGAN DARI AKSI KEKERASAN NARAPIDANA PRIA - Rahmanidar Rahmanidar (Universitas Riau Kepulauan, 2015)
Jurisdictional review of the function of women's special prisons as an effort to protect against acts of violence by male inmates in Penitentiary Institutions is 1995 on Imprisonment, namely protection, equal treatment and service, education, guidance, respect for human dignity and worth, guaranteeing the right to remain in touch with families and certain people. Rights-The rights of women prisoners under Law Number 12 of 1995 on Imprisonment are about worship, physical and spiritual care, education and teaching, health and food services, complaints and remission. The formulation of the real problem is how the legal regulation of the rights of women prisoners and how the function of women's special prisons in an effort to protect from acts of violence by male prisoners in Prison Class II A Batam. This study uses normative methods and sociological or empirical legal research, while the approach method uses normative jurisprudence. This study aims to determine the regulation of the rights of women prisoners as well as to determine the function of special prisons for women in efforts to protect from acts of violence by male prisoners. Therefore, it is hoped that the Government will always pay attention and implement Law No. 12 of 1995 on Imprisonment in Penitentiary Institutions, and the need for a separation in the environment or place between the environment of women prisoners and the environment of male prisoners so that it can avoid and prevent acts of crime and violence against women prisoners.